Children and adolescents with phenylketonuria display fluctuations in their blood phenylalanine levels. (17th August 2018) - Feldmann, R; Schallert, M; Nguyen, T; Och, U; Rutsch, F; Weglage, J
Abstract: Aim: This study examined the impact of fluctuations in metabolic control on the intelligence quotient (IQ) of children and adolescents with early, continuously treated phenylketonuria (PKU). Methods: This was a clinic‐based study carried out at University Hospital Munster, Germany, from 2015 to 2017. We investigated 49 patients (28 boys) with early treated PKU, who were aged 6–18 years with a mean age of 11.2 ± 4.1 years. All the patients were on a continuous phenylalanine‐restricted diet. Of the 49 patients, 29 (18 boys) had classic PKU and 21 patients (11 girls) had mild PKU. The patients' blood phenylalanine levels were assessed every week for 26 weeks and analysed for fluctuations, indicated by the standard deviation of the individual blood phenylalanine levels. We also assessed the concurrent Full Scale IQ (FSIQ) of the patients. Results: In patients with classic PKU, FSIQ was negatively correlated with blood phenylalanine levels, but not with level fluctuations. In patients with mild PKU, FSIQ was not correlated with blood phenylalanine levels, but was negatively correlated with level fluctuations. Conclusion: The blood phenylalanine levels of patients with mild PKU showed minor interindividual differences, which may have allowed fluctuations to exert a negative effect on the FSIQ.